Efecto del Google Classroom en la motivación de estudiantes VII ciclo en la I.E. Corpus Christi, Iquitos 2024 - Izquierdo Gonzales, Gabriela Patricia (2025)
The study aimed to evaluate the effect of the Google Classroom platform on the motivation of students of the VII cycle in the educational institution Corpus Christi English School in the city of Iquitos in the year 2024, for this a quasi-experimental design was used where the independent variable Google Classroom was used to measure the effect it had on the dependent variable student motivation, The study had a population made up of students in the seventh cycle of secondary studies of the Corpus Christi English School educational institution, which were a total of 76 students, for the sample we worked with the entire population divided into two groups of 38 each to be part of the experimental and control group, The descriptive results showed that in the pre-test both groups obtained a low motivation and in the post-test the experimental group obtained a high motivation, therefore, it is affirmed that there is no significant difference between the data collected in the pre-test of the control and experimental group and in the post-test it is confirmed that the results between the control and experimental group have a significant difference, data that are verified by applying the Mann Whitney U statistical test by obtaining a significance value of less than 0.05 in the post-test, concluding that the Google Classroom platform has a positive effect on student motivation in the educational institution Corpus Christi English School.